Randomized Comparison of the Polymer-Free Biolimus-Coated BioFreedom Stent With the Ultrathin Strut Biodegradable Polymer Sirolimus-Eluting Orsiro Stent in an All-Comers Population Treated With Percutaneous Coronary Intervention: The SORT OUT IX Trial. Issue 25 (23rd June 2020) - Jensen, Lisette Okkels; Maeng, Michael; Raungaard, Bent; Kahlert, Johnny; Ellert, Julia; Jakobsen, Lars; Villadsen, Anton Boel; Veien, Karsten Tange; Kristensen, Steen Dalby; Ahlehoff, Ole; Carstensen, Steen; Christensen, Martin Kirk; et al.
Abstract : Background: In patients with increased bleeding risk, the biolimus A9-coated BioFreedom stent, a stainless steel drug-coated stent free from polymer, has shown superiority compared with a bare-metal stent. The aim of this study was to investigate whether the BioFreedom stent is noninferior to a modern ultrathin strut biodegradable polymer cobalt-chromium sirolimus-eluting Orsiro stent in an all-comers patient population treated with percutaneous coronary intervention. Methods: The SORT OUT IX trial (Scandinavian Organization for Randomized Trials With Clinical Outcome IX), was a large-scale, registry-based, randomized, multicenter, single-blind, 2-arm, noninferiority trial. The primary end point, major adverse cardiovascular events, was defined as the composite of cardiac death, myocardial infarction not related to any segment other than the target lesion, or target lesion revascularization within 1 year, analyzed by intention-to-treat. The trial was powered to assess noninferiority for major adverse cardiovascular events of the BioFreedom stent compared with the Orsiro stent with a predetermined noninferiority margin of 0.021. Results: Between December 14, 2015 and April 21, 2017, 3151 patients were assigned to treatment with the BioFreedom stent (1572 patients, 1966 lesions) or to the Orsiro stent (1579 patients, 1985 lesions). Five patients were lost to follow-up because of emigration (99.9% follow-up rate). Mean age was 66.3±10.9, diabetes mellitus was seen in 19.3% of patients, and 53% of the patients had acute coronary syndromes. At 1 year, intention-to-treat analysis showed that 79 (5.0%) patients, who were assigned the BioFreedom stent, and 59 (3.7%), who were assigned the Orsiro stent, met the primary end point (absolute risk difference 1.29% [upper limit of one-sided 95% CI 2.50%]; P noni nferiority =0.14). Significantly more patients in the BioFreedom stent group had target lesion revascularization than those in the Orsiro stent group (55 [3.5%] vs 20 [1.3%], rate ratio 2.77 [95% CI, 1.66–4.62]; P <0.0001). Conclusions: The biolimus A9-coated BioFreedom polymer-free stent did not meet criteria for noninferiority for major adverse cardiovascular events at 12 months when compared with the ultrathin strut biodegradable polymer sirolimus-eluting Orsiro stent in an all-comers population Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT02623140. Abstract : Supplemental Digital Content is available in the text.